Phylogenetic and structural analyses of equine rotaviruses : three possible geographically related lineages - Miño, Samuel (2016)
The structural analyses revealed that the aa substitutions in VP7 are in the antigenic sites and in the VP7:VP6 interaction region. In accordance, most of the aa changes in VP6 are in the top of the protein involving antigenic and VP7:VP6 interaction sites. Interestingly, the structural analyses of VP8* showed a few aa differences in the antigenic sites and, all equine P[12] shown the same conserved aa sequence in VP8* pocket, only observed in P[12] genotype. Our study suggest the existence of geographically related equine RVA lineages and, describe the aa configuration of the VP8* pocket.